Prognostic Factors for Clinical Outcomes and Lesion Reactivation in Stage 2–3 Type 3 Macular Neovascularization Treated Using a Treat-and-Extend Regimen - Yeji Kim; Sang Min Park; Han Joo Cho; Jae Hui Kim (Retina, 2026)
Purpose: To evaluate the treatment outcomes of type 3 macular neovascularization(MNV) and identify factors associated with visual outcomes and lesion reactivation during 76 weeks of aflibercept therapy using a treat-and-extend(TAE) regimen. Methods: This post hoc analysis included 25 treatment-naïve patients with stage 2–3 type 3 MNV who participated in a previous prospective study and received aflibercept treatment for 76 weeks using a TAE regimen. The incidence and outcomes of the first lesion reactivation were assessed. Factors associated with lesion reactivation and best-corrected visual acuity(BCVA) at the final visit were evaluated. Results: Lesion reactivation occurred in 8 patients(32.0%) during the treatment period; however, no patient experienced a loss of ≥5 letters before or after the first reactivation. In multivariate analysis, BCVA at week 16 was a strong predictor of final BCVA(P